Maintenance costs of a pitch control device of a wind turbine - Carvalho, Mariana (2013)
Although the wind turbines are nowadays the principal source of wind energy production, the technical information publicly known about these machines is still very scarce. Information related to failure modes, unavailability and maintenance costs of these systems remain confidential and only the manufacturer has knowledge about them. To be able to optimize the efficiency, to guarantee the security and to negotiate better warranty and maintenance contracts, it is necessary to know more information about the operation and maintenance and replacement costs of subsystems of a wind turbine. To this end, and based on two years of operation, this paper exhaustively analyses an active power control system, of 21 identical wind turbines, installed in a wind farm in Portugal. The emphasis of this study is on its operation, availability and maintenance and replacement costs, obtaining, in particular, an estimate for the total maintenance cost of the active pitch control device, one of the most important components of the turbine, which automatically manages the position and operation of blades, according to wind direction and speed, thus maximizing gathered electrical power or stopping the operation whenever bad weather conditions exist.